The “Paulo Fraire” Educational Thinking Paradigm in the Service Learning Model in Higher Education - Ardhana Januar Mahardhani; Prihma Sinta Utami (AL-ISHLAH: Jurnal Pendidikan, 2022)
he study of writing this article is focused on discussing the concept of an educational paradigm of thinking about problems or problem-posing offered by Paulo Fraire's character in relation to the implementation of lecture activities combined with the service-learning model. The purpose of writing this article will be focused on seeing how the implementation pattern or learning stage model uses the problem-posing paradigm of Paulo Freire's thinking which will be linked to the service-learning model. The method in writing this article uses the literature review method. The literature review was carried out by analyzing journals in the 2010-2021 period related to the study of Paulo Fraire's paradigm of thinking about problem posing and theoretical studies on the implementation of service-learning. From the results of the analysis of related journals found 15 journals that can be used as a reference for the analysis. Based on the findings of the integration of the service-learning model and problem posing, it was found that 4 steps can be taken, namely: listening, action, reflection, and demonstration. Paulo Fraire's paradigm of thinking about education facing problems or problem posing is based on the phenomenon of education with the "bank system" style, in which students are like "empty souls" who passively receive explanations from the teacher in the classroom. Through this paper, it will be emphasized how the pattern or model of implementing the learning paradigm of educational thinking towards the Paulo Freire problem is offered with the service-learning model approach.